2021
DOI: 10.1038/s41467-021-24995-9
|View full text |Cite
|
Sign up to set email alerts
|

Patched regulates lipid homeostasis by controlling cellular cholesterol levels

Abstract: Hedgehog (Hh) signaling is essential during development and in organ physiology. In the canonical pathway, Hh binding to Patched (PTCH) relieves the inhibition of Smoothened (SMO). Yet, PTCH may also perform SMO-independent functions. While the PTCH homolog PTC-3 is essential in C. elegans, worms lack SMO, providing an excellent model to probe non-canonical PTCH function. Here, we show that PTC-3 is a cholesterol transporter. ptc-3(RNAi) leads to accumulation of intracellular cholesterol and defects in ER stru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…In functional terms, it is currently thought that ligand-free Ptc (Figure 1, step 6) forms a trimer [23] that undergoes conformational cycling to actively pump cholesterol from the inner leaflet of the plasma membrane to hand it off to extracellular sterol acceptors. [24,25] Consistent with such a highly conserved cholesterol transporter function of Ptc, [26] detection of four collective sterolbinding sites (S1-S4) in Ptc suggest a central hydrophobic conduit for cholesterol transport that courses from the inner leaflet of the plasma membrane to the extracellular domain [24,27,28] (Figure 1 bottom row, far right). Through this conduit, the amount of membrane cholesterol is continuously reduced but increases rapidly upon Hh binding to Ptc.…”
Section: Overview Of the Components Of The Canonical Hh Signaling Pat...mentioning
confidence: 68%
See 1 more Smart Citation
“…In functional terms, it is currently thought that ligand-free Ptc (Figure 1, step 6) forms a trimer [23] that undergoes conformational cycling to actively pump cholesterol from the inner leaflet of the plasma membrane to hand it off to extracellular sterol acceptors. [24,25] Consistent with such a highly conserved cholesterol transporter function of Ptc, [26] detection of four collective sterolbinding sites (S1-S4) in Ptc suggest a central hydrophobic conduit for cholesterol transport that courses from the inner leaflet of the plasma membrane to the extracellular domain [24,27,28] (Figure 1 bottom row, far right). Through this conduit, the amount of membrane cholesterol is continuously reduced but increases rapidly upon Hh binding to Ptc.…”
Section: Overview Of the Components Of The Canonical Hh Signaling Pat...mentioning
confidence: 68%
“…[29] The other model of Scube2-modulated Shh shedding requires that the role of Disp in Hh release must be indirect, possibly involving a Disp-modulated messenger molecule that in turn affects shedding. This messenger molecule might be plasma membrane cholesterol, as indicated by the known structural similarities between Disp and the established cholesterol pumps Ptc [26,29] and NPC1. [75] Further support for a sterol-pumping function of Disp comes from the detection of sterol-like densities in the Disp transmembrane domains, [72,76] again similar to what has been described for Ptc [28,29] and NPC1.…”
Section: Disp As a Hh Release Regulatormentioning
confidence: 99%
“…Interactions between fatty acid metabolism and innate immunity ( Anderson and Pukkila-Worley, 2020 ) or between fatty acid metabolism and Hedgehog-like signaling ( Lin and Wang, 2017 ; Del Castillo et al, 2021 ) have been frequently reported in animals, including in C. elegans . Increased C. elegans fatty acid metabolism is also strongly associated with reproduction ( Ezcurra et al, 2018 ), while a trade-off between reproduction and the mounting of effective innate immune responses has been previously established ( TeKippe and Aballay, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…(they became hypersensitive to thermal stress, Figure 3C ). Lipid metabolism is key to both immunity and the HHLS pathway since phospholipid membrane dynamics and cholesterol metabolism are critical to Hedgehog signaling (Cadena Del Castillo et al, 2021 ). Our data also suggest that grl-21 contributes to worm resistance to E. faecalis infection, together with related HRPs grl-6, grl-12, grl-22 , and grl-27 ( Figures 3B,C ), although they do not point out to specific cognate PTR receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation